Filter material, manufacturing method for the same, filter container and inclusion body

By using a biodegradable filter material composed of the first and second nonwoven fabric layers, the problem of difficulty in controlling the extraction rate of aqueous liquids in the prior art and changing the properties of the filter material during storage is solved, and the consistency of the design extraction rate is maintained for a long time after packaging.

JP2025059791APending Publication Date: 2025-04-10KURARAY KURAFLEX CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023170102
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

In the prior art, the biodegradable fiber is too aqueous, which makes it difficult to control the excessively fast filtrate rate when extracting the aqueous liquid, and during storage, changes in the physical properties of the filter material lead to the unsustainable extraction rate.

Method used

A biodegradable filter material consisting of the first and second nonwoven fabric layers is used. The diameter of the first fiber is smaller than the second layer, and at least one layer is biodegradable fiber. The density of the first layer is between 0.85-2.00 g/cm³, and the surface fiber occupies an area of ​​70% or more.

Benefits of technology

It achieves the consistency of the extraction rate during storage, ensures that the filter material maintains the designed filtrate performance for a long time after packaging, and is suitable for extraction of aqueous liquids such as coffee.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059791000001_ABST
    Figure 2025059791000001_ABST
Patent Text Reader

Abstract

To provide a filter material at least partially having a biodegradable fiber and constituted by a specific non-woven fabric layer, a manufacturing method for the filter material, a filter container using the filter material and an inclusion body.SOLUTION: A filter material in one embodiment includes a laminated body comprising a first non-woven fabric layer and a second non-woven fabric layer. Fibers constituting the first non-woven fabric layer have an average fiber diameter smaller than that constituting the second non-woven fabric layer. At least either one of the first non-woven fabric layer and the second non-woven fabric layer comprises a biodegradable fiber, and density of the first non-woven fabric layer is 0.85 g / cm3 or larger.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a filter material that has at least a portion of a biodegradable fiber and is composed of a specific nonwoven fabric layer, a method for producing the same, and a filter container and an enclosure that use the same. [Background technology]

[0002] In recent years, when extracting coffee, soup stock, etc., there has been a trend toward using filters made of nonwoven fabric sheets that contain coffee, dried bonito flakes, or other materials to be extracted. In recent years, from the perspective of environmental protection, the nonwoven fabric sheets used in such filters are required to be at least partially made of biodegradable materials.

[0003] For example, Patent Document 1 (JP 2016-168569 A) describes a fabric made of polylactic acid resin fibers having a crystallinity of 9.0% or less and a fiber diameter of 15.0 μm or less, and a basis weight of 2.0 to 30.0 g / m 2 and a layer (M layer) formed of a melt-blown nonwoven fabric sheet having a crystallinity of 30.0 to 60.0% and a fiber diameter of 35.0 μm or less, the layer being made of fibers of a polylactic acid resin and having a basis weight of 5.0 to 30.0 g / m. 2 and a layer (S layer) formed of a spunbond nonwoven fabric.

[0004] In addition, Patent Document 2 (JP 2011-157118 A) describes a food filter made of a biodegradable laminated nonwoven fabric sheet composed of long fibers and ultrafine fibers of a polylactic acid polymer, and the laminated nonwoven fabric sheet has a fiber diameter of 10 to 20 μm and a basis weight of 10 to 40 g / m 2 Long fiber nonwoven sheet with fiber diameter of 1 to 10 μm and basis weight of 1 to 10 g / m 2 At least two types of nonwoven fabric sheets of the ultrafine fiber nonwoven fabric sheet are integrated by thermocompression bonding, and the laminated nonwoven fabric sheet has a thickness of 0.02 to 0.50 mm and an air permeability of 100 to 300 cc / cm 2The food filter is characterized in that the heat seal strength is 4N / 25mm or more and the heat seal strength is 4N / 25mm or more.

[0005] Furthermore, Patent Document 3 (JP 2000-336570 A) describes a fiber liner made of a biodegradable thermoplastic polymer, having an average fiber diameter of 20 μm or less, and having an air permeability of 10 to 250 cm 3 / cm 2 The present invention discloses a sheet material for coffee extraction, which is characterized by comprising a meltblown ultrafine fiber nonwoven fabric sheet having a water absorption speed of 5 seconds or less in water at a temperature of 60°C or higher. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-168569 A [Patent Document 2] JP 2011-157118 A [Patent Document 3] JP 2000-336570 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the sheets and filters of Patent Documents 1 to 3, biodegradable fibers formed from polylactic acid polymers are used as filter materials, and these biodegradable fibers are generally highly hydrophilic. Therefore, when extracting a hydrophilic liquid from an encapsulated substance such as coffee, the fiber diameter of the biodegradable fibers or the basis weight of the nonwoven fabric sheet is adjusted to control the extraction rate from the filter so that the extraction rate of the hydrophilic liquid does not become too fast.

[0008] On the other hand, when a substance such as coffee is encapsulated in a filter material and the encapsulated body is distributed on the market, it has become clear that there is a problem that the physical properties of the filter material change due to the encapsulated substance during storage, possibly due to the high hydrophilicity of biodegradable fibers, and the extraction rate at the time of encapsulation cannot be maintained. Therefore, there is a demand for a filter material that can maintain the extraction rate set at the time of encapsulation even when stored for a specified period of time.

[0009] Therefore, an object of the present invention is to provide a filter material that can maintain the filter properties set at the time of encapsulation even when the material is stored for a predetermined period of time after encapsulation. [Means for solving the problem]

[0010] That is, the present invention can be configured in the following manner. [Aspect 1] A laminate including a first nonwoven fabric layer and a second nonwoven fabric layer, the fibers constituting the first nonwoven fabric layer have an average fiber diameter smaller than that of the fibers constituting the second nonwoven fabric layer; At least one of the first nonwoven fabric layer and the second nonwoven fabric layer is made of biodegradable fibers, The density of the first nonwoven fabric layer is 0.85 g / cm 3 or more (e.g., 0.85 to 2.00 g / cm 3 , preferably 0.90 g / cm 3 ~2.00g / cm 3 , more preferably 0.95 g / cm 3 ~2.00g / cm 3 ) a filter material. [Aspect 2] A laminate including a first nonwoven fabric layer and a second nonwoven fabric layer, the fibers constituting the first nonwoven fabric layer have an average fiber diameter smaller than that of the fibers constituting the second nonwoven fabric layer; At least one of the first nonwoven fabric layer and the second nonwoven fabric layer is made of biodegradable fibers, A filter material, in which at least one surface of the first nonwoven fabric layer has a fiber-occupied area of ​​70% or more (eg, 70 to 95%, preferably 73 to 93%, more preferably 75 to 90%). [Aspect 3] The filter material according to aspect 2, wherein at least one surface of the first nonwoven fabric layer has a fiber-occupied area of ​​70% or more (e.g., 70 to 95%, preferably 73 to 93%, and more preferably 75 to 90%) and an occupancy rate of the contour lines of the fibers on that surface of 20.0% or more (e.g., 20.0 to 50.0%, preferably 21.0 to 45.0%, and more preferably 23.0 to 40.0%). Aspect 4 The filter material according to any one of aspects 1 to 3, wherein the first nonwoven fabric layer has a thickness of 0.1 to 12.0 μm (preferably 1.0 to 11.0 μm, more preferably 2.0 to 10.5 μm). Aspect 5 A filter material according to any one of aspects 1 to 4, wherein the first nonwoven fabric layer has a basis weight of 1 to 14 g / m 2 (Preferably 3 to 13 g / m 2 , more preferably 5 to 12 g / m 2 ) a filter material. Aspect 6 The filter material according to any one of aspects 1 to 5, wherein the thickness of the first nonwoven fabric layer is 2 to 15% (preferably 3 to 13%, and more preferably 5 to 11%) of the thickness of the laminate. Aspect 7 The filter material according to any one of the first to sixth aspects, wherein the first nonwoven fabric layer is made of a meltblown nonwoven fabric. Aspect 8 The filter material according to any one of aspects 1 to 7, wherein the second nonwoven fabric layer is made of a spunbond nonwoven fabric. Aspect 9 A filter material according to any one of the first to eighth aspects, which is used for filtering oil-containing solid matter. Aspect 10 The filter material according to any one of aspects 1 to 9, wherein the first nonwoven fabric layer and the second nonwoven fabric layer both contain biodegradable fibers. Aspect 11 11. The filter material of embodiment 10, wherein the biodegradable fibers comprise polylactic acid fibers. Aspect 12 A filter container comprising the filter material according to any one of the first to eleventh aspects, the first nonwoven fabric layer being disposed on an inner side. Aspect 13 An encapsulation body comprising the filter material according to any one of the first to eleventh embodiments and a substance to be encapsulated, wherein the substance to be encapsulated is in contact with a first nonwoven fabric layer. Aspect 14 A method for producing a filter material including a laminate composed of a first nonwoven fabric layer and a second nonwoven fabric layer, comprising: Providing a first nonwoven fabric sheet and a second nonwoven fabric sheet; and a step of integrating the first nonwoven fabric sheet and the second nonwoven fabric sheet to obtain a laminate composed of a first nonwoven fabric layer and a second nonwoven fabric layer, the fibers constituting the first nonwoven fabric sheet have an average fiber diameter smaller than that of the fibers constituting the second nonwoven fabric sheet; At least one of the first nonwoven fabric sheet and the second nonwoven fabric sheet is made of biodegradable fibers, The method for producing a filter material, wherein the first nonwoven fabric sheet is in a pressed state. Aspect 15 Aspect 15. A method for producing a filter material according to aspect 14, wherein the step of preparing a first nonwoven fabric sheet comprises a step of obtaining a first nonwoven fabric sheet by pressing. Aspect 16 16. A method of producing a filter material according to any one of claims 14 to 15, wherein the first nonwoven sheet is a pressed meltblown nonwoven. Effect of the Invention

[0011] According to the present invention, the filter material can maintain the filter properties set at the time of encapsulation even when the filter material is stored for a predetermined period of time after encapsulating the substance. [Brief description of the drawings]

[0012] The present invention will be more clearly understood from the following description of preferred embodiments with reference to the accompanying drawings. However, the embodiments and drawings are merely for illustration and explanation, and should not be used to define the scope of the present invention, which is defined by the appended claims. [Figure 1A] 1 is an electron microscope photograph (magnification: 500) of the surface (non-embossed compression bonded portion) of the first nonwoven fabric layer in Example 1 of the present invention. [Figure 1B] 1B is a photograph obtained by subjecting the electron microscope photograph of FIG. 1A to image processing in order to calculate the fiber-occupied area. [Figure 1C] This is a photograph in which the electron microscope photograph of FIG. 1A was subjected to image processing in order to calculate the occupancy rate of the fiber contour line. [Figure 2A] 2 is an electron microscope photograph (magnification: 500) of the surface of the first nonwoven fabric layer in Comparative Example 1 of the present invention. [Figure 2B] This is a photograph in which the electron microscope photograph of FIG. 2A was subjected to image processing in order to calculate the fiber-occupied area. [Figure 3A] 1 is an electron microscope photograph (magnification: 500) of the surface (non-embossed compression bonded portion) of the first nonwoven fabric layer in Comparative Example 5 of the present invention. [Figure 3B] This is a photograph in which the electron microscope photograph of FIG. 3A was subjected to image processing in order to calculate the fiber-occupied area. [Figure 3C] This is a photograph in which the electron microscope photograph of FIG. 3A was subjected to image processing in order to calculate the occupancy rate of the fiber contour line. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] One aspect of the present invention is a method for producing a filter material including a laminate composed of a first nonwoven fabric layer and a second nonwoven fabric layer, the method comprising at least the steps of preparing a first nonwoven fabric sheet and a second nonwoven fabric sheet, and integrating the first nonwoven fabric sheet and the second nonwoven fabric sheet to obtain a laminate composed of the first nonwoven fabric layer and the second nonwoven fabric layer. In addition, at least one of the first nonwoven fabric sheet and the second nonwoven fabric sheet is made of biodegradable fibers, preferably, at least the first nonwoven fabric sheet is made of biodegradable fibers, and more preferably, both the first nonwoven fabric sheet and the second nonwoven fabric sheet are made of biodegradable fibers.

[0014] (Biodegradable fiber) The biodegradable fibers are not particularly limited as long as they are biodegradable, but preferred biodegradable fibers include cellulose-based fibers, polyvinyl alcohol-based fibers, and aliphatic polyester-based fibers. Examples of cellulose-based fibers include natural fibers (cotton, hemp, various pulps, etc.), regenerated fibers (e.g., rayon, polynosic, cupra, lyocell, etc.), semi-synthetic fibers (e.g., cellulose acetate), and synthetic fibers. Examples of polyvinyl alcohol-based fibers include fibers formed from polyvinyl alcohol, ethylene-vinyl alcohol copolymers, etc. Examples of aliphatic polyester fibers include fibers formed from polylactic acid, polyhydroxyalkanoate, polyglycolic acid, polyethylene succinate, polybutylene succinate, polyethylene terephthalate succinate, polyethylene terephthalate adipate, polybutylene succinate adipate, polybutylene terephthalate adipate, poly-3-hydroxybutylene valerate, polycaprolactone, modified products thereof, or blends thereof. These biodegradable fibers may be used alone or in combination of two or more. Among these biodegradable fibers, polylactic acid fibers, polybutylene succinate fibers, etc. are preferred.

[0015] The first nonwoven fabric layer and the second nonwoven fabric layer may also contain non-biodegradable fibers, and examples of such fibers include synthetic fibers spun from fiber-forming resins by known techniques. Examples of fiber-forming resins include polyolefin resins (poly-C such as polyethylene and polypropylene), 2-4 Examples of the fiber-forming resin include olefin-based resins, polyvinyl chloride-based resins (polyvinyl chloride, polyvinylidene chloride, etc.), general-purpose polyester-based resins (polyalkylene arylate-based resins such as polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate), polyamide-based resins (aliphatic polyamide-based resins such as polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, and polyamide 612), polyurethane-based resins (urethane-based polymers obtained by reacting a polyol component such as polyether polyol or polyester polyol with a polyisocyanate component), and acrylic resins. These fiber-forming resins can be used alone or in combination of two or more. Among these, from the viewpoint of forming a nonwoven fabric sheet directly connected to spinning, the fiber-forming resin is preferably a polyolefin-based resin, a polyester-based resin, a polyamide-based resin, or a polyurethane-based resin, and particularly preferably a polypropylene-based resin.

[0016] These fibers may contain other conventional additives, such as stabilizers (heat stabilizers such as copper compounds, ultraviolet absorbers, light stabilizers, antioxidants, etc.), antibacterial agents, deodorants, fragrances, colorants (dyes and pigments, etc.), fillers, flame retardants, chargeability improvers (hindered amines, etc.), antistatic agents, conductive agents, plasticizers, lubricants, crystallization rate retarders, etc., within the scope of the present invention. These additives can be used alone or in combination of two or more. These additives can be selected depending on the type, and are, for example, 0.01 to 30 parts by mass, preferably 0.1 to 20 parts by mass, more preferably 0.3 to 10 parts by mass (particularly 0.5 to 5 parts by mass) relative to 100 parts by mass of the polymer component forming the fiber.

[0017] (Preparation of first and second nonwoven fabric sheets) The first nonwoven fabric sheet and the second nonwoven fabric sheet are not particularly limited in structure as long as the object of the present invention can be achieved, and may be a wet-laid or dry-laid nonwoven fabric, but a direct-spun nonwoven fabric is preferred from the viewpoint of reducing fiber dropout. Examples of the direct-spun nonwoven fabric include spunbond nonwoven fabric and meltblown nonwoven fabric.

[0018] A meltblown nonwoven fabric is formed by blowing a polymer discharged from a nozzle of a spinneret with a jet stream of high-temperature gas, forming thin fibers, and depositing them on a support such as a collection net. The polymer discharged from the spinneret may have a single hole discharge amount of, for example, 0.05 to 1.0 g / hole, preferably 0.1 to 0.8 g / hole, and more preferably about 0.2 to 0.6 g / hole. The single hole diameter may be, for example, 100 to 800 μm, preferably 150 to 700 μm, and more preferably 200 to 600 μm.

[0019] Spunbond nonwoven fabrics are formed by cooling the polymer extruded from the nozzles of a spinneret in a cold air chamber while pulling the polymer at high speed with an air jet or stretching the fibers with rolls, collecting the polymer as a fiber web on a net conveyor, and then pressing the fibers together with heated rolls.

[0020] The first nonwoven fabric sheet is composed of fibers having an average fiber diameter smaller than that of the fibers constituting the second nonwoven fabric sheet, and therefore may preferably be a meltblown nonwoven fabric. The second nonwoven fabric sheet is preferably a spunbond nonwoven fabric, since it is made of fibers having a larger average fiber diameter than the fibers constituting the first nonwoven fabric layer.

[0021] The step of preparing the first nonwoven fabric sheet may be a step of preparing a nonwoven fabric sheet that has already been pressed as the first nonwoven fabric sheet, or the step of preparing the first nonwoven fabric sheet may be a step of pressing an unpressed nonwoven fabric to obtain the first nonwoven fabric sheet.

[0022] The pressing treatment can be appropriately set depending on the structure of the nonwoven fabric sheet before the pressing treatment, and is carried out, for example, by calendaring.

[0023] When performing the calendering, the pressure can be appropriately set depending on the pressure of the nonwoven fabric sheet. For example, the calendering is performed between a pair of a rubber roll and a metal roll at a linear pressure of, for example, 30 to 60 kg / cm, preferably 30 to 50 kg / cm, and more preferably 35 to 50 kg / cm.

[0024] The temperature during the calendaring can be appropriately set depending on the type of nonwoven fabric sheet, but for example, when the lowest melting point or glass transition temperature of the fibers constituting the nonwoven fabric sheet is taken as T, it may be T-90° C. to T-20° C., preferably T-80° C. to T-30° C. Here, when the resin forming the fibers is a crystalline resin, the melting point can be used as the reference, and when it is an amorphous resin, the glass transition temperature can be used as the reference, and the melting point and glass transition temperature are values ​​measured by JIS K 7121-2012 differential scanning calorimetry (DSC).

[0025] (integration process) In the step of integrating the first nonwoven fabric sheet and the second nonwoven fabric sheet, the first nonwoven fabric sheet and the second nonwoven fabric sheet are overlapped and integrated together. For example, when the first nonwoven fabric sheet and the second nonwoven fabric sheet are integrated together, it is preferable that the first nonwoven fabric sheet and the second nonwoven fabric sheet are integrated together while having at least a portion where they are not directly fused together.

[0026] The step of integrating the first nonwoven fabric sheet and the second nonwoven fabric sheet can be carried out by a known method. From the viewpoint of laminating and integrating the sheets without the use of adhesives, however, it is preferable to fuse and integrate the two sheets by embossing, ultrasonic treatment, or the like.

[0027] In the embossing process, the sheet is sandwiched between a pair of embossing rolls or a combination of an embossing roll and a flat roll, and the protruding parts of the embossments are thermally compressed to fuse the first sheet for nonwoven fabric sheet and the second sheet for nonwoven fabric sheet.

[0028] In the ultrasonic treatment, the sheets are sandwiched between an ultrasonic oscillator and an embossing roll, and the protruding portions of the embossing are thermocompression-bonded to fuse the first sheet for nonwoven fabric sheet and the second sheet for nonwoven fabric sheet.

[0029] From the viewpoint of maintaining the high density structure of the first nonwoven fabric layer, it is preferable that the pressure-bonded surfaces of the embossed convex portions are appropriately spaced apart, and for example, the average separation distance between the embossed pressure-bonded surfaces may be, for example, 0.5 to 4.0 mm, preferably 0.8 to 3.5 mm, and more preferably 1.0 to 3.0 mm. Here, the separation distance means the distance between the pressure-bonded surfaces of the highest part of the embossing roll surface per embossing roll pattern present on an arbitrarily selected straight line in the MD direction of the first nonwoven fabric layer, and the average separation distance means the average separation distance between the embossed pressure-bonded surfaces in successive embossing roll patterns.

[0030] In the filter material, from the viewpoint of ensuring void portions, it is preferable that void portions and bonded portions (particularly fused portions when embossing or ultrasonic treatment is performed) are alternately present in the laminate of the first nonwoven fabric layer and the second nonwoven fabric layer. The ratio of the embossed and compressed surface to the entire surface of the filter material may be, for example, 3 to 30%, preferably 5 to 25%, and more preferably 10 to 20%.

[0031] (filter material) One aspect of the present invention includes a laminate composed of a first nonwoven fabric layer and a second nonwoven fabric layer, wherein fibers constituting the first nonwoven fabric layer have an average fiber diameter smaller than that of fibers constituting the second nonwoven fabric layer, at least one of the first nonwoven fabric layer and the second nonwoven fabric layer is composed of biodegradable fibers, and the density of the first nonwoven fabric layer is 0.85 g / cm 3 That is all about the filter material.

[0032] The density of the first nonwoven layer is preferably 0.90 g / cm 3 More preferably, 0.95 g / cm 3 By increasing the density of the first nonwoven fabric layer, it is possible to suppress a change in the extraction rate from the encapsulated substance caused by a change in the physical properties of the filter material after encapsulation. The upper limit of the density of the first nonwoven fabric layer is not particularly limited as long as it does not impede release, but it is, for example, 2.00 g / cm. 3 Here, the density is a value measured by the method described in the examples below.

[0033] One aspect of the present invention is a filter material including a laminate composed of a first nonwoven fabric layer and a second nonwoven fabric layer, wherein the fibers constituting the first nonwoven fabric layer have an average fiber diameter smaller than the fibers constituting the second nonwoven fabric layer, at least one of the first nonwoven fabric layer and the second nonwoven fabric layer is composed of biodegradable fibers, and at least one surface of the first nonwoven fabric layer has a fiber-occupied area of ​​70% or more.

[0034] The fiber-occupied area on at least one surface of the first nonwoven fabric layer may be preferably 73% or more, more preferably 75% or more. The upper limit of the fiber-occupied area of ​​the first nonwoven fabric layer is not particularly limited as long as it does not impede releasability, but may be, for example, 90% or less. Here, the fiber-occupied area is a value measured by the method described in the examples below.

[0035] The fiber contour occupancy rate on the surface of the first nonwoven fabric layer measured for the fiber occupancy area may be, for example, 20.0% or more, preferably 21.0% or more, and more preferably 23.0% or more. The upper limit of the fiber contour occupancy rate on the surface of the first nonwoven fabric layer is not particularly limited as long as it does not impede releasability, but may be, for example, 50.0% or less. Here, the fiber contour occupancy rate is a value measured by the method described in the Examples below.

[0036] The size of the fiber occupation area indicates the proportion of fibers present on the surface of the first nonwoven fabric layer, and the larger the fiber occupation area, the higher the density of the fibers. When the fibers are in a high density state, the aggregated fibers can obstruct the passage of liquid through the first nonwoven fabric layer, and the liquid extraction speed can be slowed down.

[0037] Furthermore, the size of the fiber contour line occupancy indicates the proportion of fibers that are not fused or bonded to each other. When fibers are densely aggregated and fused to each other, the fused fibers cannot be detected as contours. Therefore, the larger the fiber contour line occupancy rate, the less fused or bonded the fibers are.

[0038] When the fibers are densely aggregated and there is little fusion between the fibers, the number of introduction paths through which the liquid passes through the first nonwoven fabric layer can be increased, thereby improving the controllability of the liquid extraction rate.

[0039] The average fiber diameter of the fibers constituting the first nonwoven fabric layer may be, for example, 10 μm or less, preferably 8 μm or less, more preferably 7 μm or less. The lower limit of the average fiber diameter is not particularly limited, but may be, for example, 1 μm or more. The average fiber diameter is a value measured by the method described in the examples below.

[0040] The thickness of the first nonwoven fabric layer may be, for example, 0.1 to 12.0 μm, preferably 1.0 to 11.0 μm, and more preferably 2.0 to 10.5 μm, from the viewpoint of controlling the extraction rate, etc. Here, the thickness is a value measured by the method described in the examples below.

[0041] The basis weight of the first nonwoven fabric layer is, for example, 1 to 14 g / m2 in order to control the extraction speed, etc. 2 and preferably 3 to 13 g / m 2 , more preferably 5 to 12 g / m 2 Here, the basis weight is a value measured by the method described in the examples described later.

[0042] The porosity of the first nonwoven fabric layer may be, for example, 5 to 35%, preferably 10 to 30%, and more preferably 13 to 28%, in order to control the extraction rate, etc. Here, the porosity is a value measured by the method described in the examples below.

[0043] The average fiber diameter of the fibers constituting the second nonwoven fabric layer is not particularly limited as long as it is larger than the average fiber diameter of the fibers constituting the first nonwoven fabric layer, and may be, for example, 1.5 to 10 times, more preferably 3 to 9 times, and further preferably 4 to 8 times, the average fiber diameter of the fibers constituting the first nonwoven fabric layer. The average fiber diameter is a value measured by the method described in the Examples below.

[0044] The thickness of the second nonwoven fabric layer may be set in relation to the first nonwoven fabric layer, and from the viewpoint of achieving both ease of handling and extractability of the filter material, may be, for example, 5 to 20 times, more preferably 6 to 18 times, and even more preferably 7 to 15 times, the thickness of the first nonwoven fabric layer. The thickness of the nonwoven fabric layer is a value measured by the method described in the Examples below.

[0045] The basis weight of the second nonwoven fabric layer is, for example, 5 to 25 g / m from the viewpoint of handling. 2 and preferably 7 to 23 g / m 2 , more preferably 10 to 20 g / m 2 Here, the basis weight is a value measured by the method described in the examples described later.

[0046] The density of the second nonwoven fabric layer is set to 0.20 g / cm from the viewpoint of suppressing clogging caused by the nonwoven fabric sheet. 3 or less, preferably 0.18 g / cm 3 Less than or equal to 0.15 g / cm 3 The lower limit of the density of the second nonwoven fabric layer is not particularly limited as long as it does not excessively suppress the release property, but may be, for example, 0.05 g / cm3 or less. 3The density here is a value measured by the method described in the examples below.

[0047] The air permeability of the laminate composed of the first nonwoven fabric layer and the second nonwoven fabric layer is, for example, 5 to 25 cc / cm 2 / sec, preferably 7 to 23cc / cm 2 / sec, more preferably 10-20cc / cm 2 Here, the air permeability is a value measured by the method described in the examples below.

[0048] From the viewpoint of ease of handling, the thickness of the laminate composed of the first nonwoven fabric layer and the second nonwoven fabric layer may be, for example, 110 to 200 μm, preferably 115 to 180 μm, and more preferably 120 to 170 μm. Here, the thickness is a value measured by the method described in the examples described later.

[0049] Furthermore, the thickness of the first nonwoven fabric layer relative to the thickness of the laminate may be, for example, 2 to 15%, preferably 3 to 13%, and more preferably 5 to 11%.

[0050] (Filter vessels and enclosures) The filter material can be used as a filter container. For example, a filter material of a desired size can be formed into a bag shape by a known or conventional method and used as a filter container.

[0051] Furthermore, it is also possible to place a substance to be encapsulated in a filter container, seal it, and use it as an encapsulated body in which the substance to be encapsulated is contained inside the filter container.

[0052] The arrangement of the nonwoven fabric layers of the filter container can be appropriately selected depending on the application, and for example, the filter material may be arranged so that the hydrophilic liquid flows from the first nonwoven fabric layer to the second nonwoven fabric layer, or the filter material may be arranged so that the hydrophilic liquid flows from the second nonwoven fabric layer to the first nonwoven fabric layer. From the viewpoint of controlling the outflow of the hydrophilic liquid, it is preferable to arrange the filter material so that the hydrophilic liquid flows from the first nonwoven fabric layer to the second nonwoven fabric layer. In this case, for example, when the substance to be enclosed is enclosed inside the filter container, it is preferable that the filter container has the first nonwoven fabric layer on the inside of the second nonwoven fabric layer.

[0053] The first nonwoven fabric layer may be in contact with the substance to be encapsulated, or the second nonwoven fabric layer may be in contact with the substance to be encapsulated. From the viewpoint of controlling the outflow of the hydrophilic liquid, it is preferable that the first nonwoven fabric layer is in contact with the substance to be encapsulated. In this case, the extraction rate of the extractable substance from the substance to be encapsulated can be slowed down by the first nonwoven fabric layer.

[0054] When producing the filter container and the enclosed body, the filter material may be bonded using an adhesive, but from the viewpoint of adhesive-free bonding, the filter material may be bonded by sewing, heat fusion, high-frequency bonding, ultrasonic bonding, or the like.

[0055] The filter container and the enclosure may be composed of a filter material and, if necessary, other members, etc. The other members may be a frame for supporting the filter container and the enclosure, a grip for the filter container and the enclosure, etc.

[0056] The encapsulated substance may be various solids depending on the application, for example, foodstuffs such as coffee, tea leaves, powder for soup stock (dried bonito flakes, powder for sardines), medicines such as herbal medicines, sustained-release drugs, etc. For example, the encapsulated substance may be an oil-containing solid (for example, coffee, powder for soup stock, etc.).

[0057] In the inclusion body, it is preferable that the first nonwoven fabric layer is in contact with the encapsulated substance from the viewpoint of controlling the release property. In particular, when the encapsulated substance is an oil-containing solid, the inclusion body containing the oil-containing solid inside generally has the oil derived from the oil-containing solid adhered to the filter fiber surface during storage, so that the fiber surface is coated with oil. If an oil film is present on the fiber surface, when the extract is released from the inclusion body using a water-soluble medium, the liquid containing the extract flows quickly through the oil film, so that it is difficult to slow down the extraction rate of the oil-containing solid in the inclusion body.

[0058] On the other hand, when the density of the first nonwoven fabric layer is controlled, even if an oil film is formed on the surface of the first nonwoven fabric layer, the high-density structure can slow down the extraction rate of the liquid containing the extract, thereby increasing the release concentration of the extract.

[0059] For example, when the substance to be encapsulated is coffee, the coffee extraction rate can be slowed down, so that the concentration of the coffee extract can be increased, and the extracted coffee has a strong taste and excellent flavor.

[0060] Furthermore, because the filter material is made of a biodegradable polymer, it is possible to encapsulate a drug and implant it in the body. In this case, not only can the encapsulated substance be slowly released within the body using body fluids, but if the filter material is made of a bioabsorbable biodegradable polymer, it can be decomposed and absorbed within the body after the encapsulated substance has been released, without the need for surgery to remove the filter material. EXAMPLES

[0061] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples and comparative examples, various physical properties were measured by the following methods.

[0062] [Average fiber diameter] The surface of the test piece was photographed by SEM (magnification 1000 times), and the diameters of 100 random fibers in the photograph were measured for each of the first fiber layer and the second fiber layer, and the average value was defined as the average fiber diameter. Note that, when the fiber diameter of a single fiber is biased, the fiber diameter of that fiber was defined as the average value of the diameter at the maximum diameter point and the diameter at the minimum diameter point.

[0063] [Thickness of the first and second fiber layers] The test piece was cut with a sharp razor in a direction perpendicular to the flow direction (or MD) of the fibers of the test piece, and the cross section was observed with a scanning electron microscope (SEM) to measure the distance between the front and back surfaces of the fine fiber layer, which is the first fiber layer. Measurements were performed at 10 equally spaced points, and the average value of the 10 points was taken as the thickness of the first fiber layer. If there were any parts in the filter material where the shape of the first fiber layer was clearly deformed due to post-processing such as being composited by heat embossing and compression bonding, such deformed parts were avoided when making measurements. The second fiber layer was also calculated in the same way.

[0064] [Density of the first and second fiber layers] The weight was calculated from the basis weight and thickness of the first fiber layer. The weight was similarly calculated for the second fiber layer.

[0065] [Porosity of the first fiber layer] It was calculated from the density of the first fiber layer (ρ1) and the density of the resin used in the first fiber layer (ρr) according to the following formula. Porosity (%) = (1-ρ1 / ρr)×100

[0066] [Fiber area] The surface of the first fiber layer of the test piece, where there was no thermal bonding due to embossing, was photographed at 500x magnification using a scanning electron microscope (SEM). The image was imported into a digital microscope DSX1000 (OLYMPUS), and the image was binarized (binarized) with a threshold value of 128 using the basic application software DSX10-BSW, and each pixel (number of pixels) was quantified. In terms of brightness, pixels with a brightness value of 0 were determined to be non-fiber-occupied parts, and pixels with a brightness value of 1 were determined to be fiber-occupied parts. The proportion of the fiber occupied area was calculated by the following formula: The measurement was performed at 10 points, and the average value was used. Fiber Occupied Area (%) = (number of pixels in fiber-occupied area / total number of pixels) x 100

[0067] [Fiber outline coverage] The same image as that used to calculate the fiber occupancy area was imported into a digital microscope DSX1000 (OLYMPUS), and the basic application software DSX10-BSW was used to convert the image into two gradations (binarization) with a threshold value of 128, and each pixel (number of pixels) was quantified. A contour extraction operation was then performed, and pixels with a brightness value of 1 were counted as the contour area and pixels with a brightness value of 0 as the non-contour area, and the contour occupancy rate was calculated using the following formula. Measurements were performed at three locations, and the average value was used. Contour coverage (%) = (number of pixels in outline area / total number of pixels) x 100

[0068] [Weight per unit area of ​​laminate] The area and weight of the sheet-shaped test piece were measured, and the weight was calculated for each 1 m 2 The weight was converted to the weight per unit area and used as the basis weight.

[0069] [Laminate thickness] The test piece was clamped under the condition that a load of 20 gf was applied to an indenter having a diameter of 16 mm, and the thickness was measured.

[0070] [Laminate Density] It was calculated from the basis weight and thickness of the test piece.

[0071] [Air permeability of laminate (cc / cm 2 / sec)] According to JIS L 1096:2010, 6.27.1 (Method A: Frazier method), three test pieces were used, and for each test piece, an air permeability measuring device (FX3300, manufactured by TEXTEST (Switzerland)) was used to measure the air permeability of the test piece over an area of ​​38 cm. 2 The air permeability was measured under the condition of a measuring pressure of 125 Pa, and the average air permeability measured for each of the three sheets was regarded as the air permeability of the laminate.

[0072] [Extraction speed] <Extraction rate before storage> A test piece cut into a 10 cm square was placed in a cylinder with an inner diameter of 5 cm, and 5 g of ground coffee beans were placed in. Boiling water was poured in, and the time it took for 200 cc to pass through the cylinder was measured. The time it took for 200 cc to pass through was recorded as the extraction rate before storage. <Extraction rate after storage> A test piece cut into a 10 cm square was wrapped around 5 g of ground coffee beans so that the first fiber layer of the test piece was in direct contact with the test piece. This was then placed in a polyethylene bag, sealed with tape, and left to stand for 5 days at a temperature of 70°C and a humidity of 50%. Thereafter, the test piece was removed from the bag, the coffee beans were shaken off, and the extraction rate was measured in the same manner as before storage.

[0073] [Example 1] Using a meltblown nonwoven fabric manufacturing device, polylactic acid resin (Luminy (trademark) L130) was spun at a single hole output of 0.2 g / min and a spinning temperature of 290°C with a hole (single hole diameter: 300 μm). Hot air at a temperature of 300°C was blown onto the spinning material, which was then scattered onto a conveyor and collected to produce an ultrafine fiber web (basis weight: approximately 10 g / m 2 The ultrafine fiber web was subjected to a calendaring treatment using a rubber roll and a metal flat roll, the metal flat roll being heated to 100° C. and sandwiched under a linear pressure of 40 kg / cm, to obtain a first nonwoven fabric sheet. The obtained first nonwoven fabric sheet and a spunbond nonwoven fabric mainly composed of polylactic acid (Asahi Kasei Ecorise S05015; average fiber diameter 16.1 μm) were sandwiched between an embossing roll and a flat roll and thermally bonded by thermal embossing (average separation distance in MD direction: 2.7 mm; bonding area: 15%) to obtain a composite filter.

[0074] 1A to 1C show an electron microscope photograph (FIG. 1A) of the surface (non-embossed surface) of the first nonwoven fabric layer, a processed image (FIG. 1B) for calculating the fiber-occupied area, and a processed image (FIG. 1C) for calculating the fiber contour line occupancy rate. As shown in FIGS. 1A to 1C, the fibers constituting the first nonwoven fabric layer are densely aggregated, so the fiber-occupied area value was 80.9%. In addition, because there is little fiber fusion between the ultrafine fibers constituting the first nonwoven fabric layer, the fiber contour line occupancy rate was 24.1%.

[0075] [Comparative Example 1] The ultrafine fiber web obtained in Example 1 and a spunbond nonwoven fabric mainly composed of polylactic acid (Asahi Kasei Ecorise S05015) were overlapped as they were, sandwiched between an embossing roll and a flat roll, and both were thermally bonded by thermal embossing. Further, using a rubber roll and a metal flat roll, the metal flat roll was heated to 100°C, and the fabric was sandwiched under a linear pressure of 40 kg / cm to perform a calendaring treatment, thereby obtaining a composite filter.

[0076] 2A and 2B show an electron microscope photograph (FIG. 2A) of the surface of the first nonwoven fabric layer, and a processed image for calculating the fiber-occupied area. As shown in FIG. 2A and 2B, the fibers constituting the first nonwoven fabric layer were not aggregated, and the value occupied by the fiber-occupied area was 58.9%.

[0077] [Comparative Example 2] A laminated sheet with ultrafine fibers having an average fiber diameter of 2.60 μm was obtained in the same manner as in Example 1, except that ultrafine fibers were collected on a conveyor on which a spunbond nonwoven fabric (Asahi Kasei Ecorise S05015; average fiber diameter 16.1 μm) mainly composed of polylactic acid was placed. The sheet thus obtained was subjected to a calendar treatment using a rubber roll and a metal flat roll, with the metal flat roll heated to 100° C. and sandwiched under a linear pressure of 40 kg / cm to obtain a composite filter.

[0078] [Comparative Example 3] The composite filter obtained in Comparative Example 2 was further sandwiched between an embossing roll and a flat roll and heat-pressed by heat embossing.

[0079] [Comparative Example 4] Using a meltblown nonwoven fabric manufacturing device, polylactic acid resin (Luminy (trademark) L130) was spun at a spinning temperature of 290°C, and hot air at a temperature of 300°C was applied to the spinning resin, which was scattered on a conveyor on which a spunbond nonwoven fabric mainly composed of polylactic acid was placed, and collected to obtain a laminated sheet. The sheet thus obtained was sandwiched between a rubber roll and a metal flat roll, the metal flat roll was heated to 100°C, and a linear pressure of 40 kg / cm was applied. The clearance between the rubber roll and the metal flat roll was adjusted so that the sheet had a thickness of about 100 μm, and the sheet was subjected to a calendaring process to obtain a composite filter.

[0080] [Comparative Example 5] The ultrafine fiber web obtained in Example 1 and a spunbond nonwoven fabric (Asahi Kasei Ecorise S05015) were overlapped as they were, and sandwiched between an embossing roll and a flat roll to thermally bond the two together by thermal embossing to obtain a composite filter.

[0081] 3A to 3C show an electron microscope photograph (FIG. 3A) of the surface (non-embossed surface) of the first nonwoven fabric layer, a processed image (FIG. 3B) for calculating the fiber-occupied area, and a processed image (FIG. 3C) for calculating the fiber contour occupancy rate. As shown in FIGS. 3A to 3C, the fibers constituting the first nonwoven fabric layer are not aggregated, and the fiber-occupied area value is 64.1%. In addition, in FIG. 3C, the fibers are not aggregated to begin with, so the fiber contour occupancy rate is 17.6%.

[0082] [Table 1]

[0083] As shown in Table 1, in Example 1, despite the use of biodegradable fibers, the extraction rate hardly changes before and after the encapsulated substance is stored. Also, in Example 1, the extraction rate from the encapsulated substance is slow both before and after storage of the encapsulated substance, and it is expected that the use of such a filter material will allow the coffee components to be extracted slowly, resulting in a coffee with a strong taste and excellent flavor. On the other hand, in Comparative Examples 1 to 5, the extraction rate almost doubled after storage, so the extraction rate designed at the time of encapsulation could not be reproduced. Also, in Comparative Examples 1, 4, and 5, the extraction rate was fast even at the time of encapsulation, so the coffee extract could not be extracted thoroughly in the first place, and the extracted coffee is expected to have a weak taste and poor flavor. [Industrial Applicability]

[0084] The filter material of the present invention has biodegradable fibers at least in part and is therefore biodegradable, and can be used, for example, as an encapsulated body in which various substances are encapsulated within the filter material.

[0085] As described above, the preferred embodiments of the present invention have been described. However, various additions, modifications, and omissions can be made without departing from the spirit of the present invention, and such additions, modifications, and omissions are also included within the scope of the present invention.

Claims

1. A laminate including a first nonwoven fabric layer and a second nonwoven fabric layer, The fibers constituting the first nonwoven fabric layer have an average fiber diameter smaller than that of the fibers constituting the second nonwoven fabric layer, At least one of the first nonwoven fabric layer and the second nonwoven fabric layer is made of biodegradable fibers, The density of the first nonwoven fabric layer is 0.85 g / cm 3 That's it, filter material.

2. A laminate including a first nonwoven fabric layer and a second nonwoven fabric layer, The fibers constituting the first nonwoven fabric layer have an average fiber diameter smaller than that of the fibers constituting the second nonwoven fabric layer, At least one of the first nonwoven fabric layer and the second nonwoven fabric layer is made of biodegradable fibers, A filter material, wherein at least one surface of the first nonwoven fabric layer has a fiber-occupied area of ​​70.0% or more.

3. 3. The filter material according to claim 2, wherein at least one surface of the first nonwoven fabric layer has a fiber occupation area of ​​70.0% or more, and an occupation rate of the contour lines of the fibers present on said surface is 20.0% or more.

4. 3. The filter material according to claim 1, wherein the first nonwoven fabric layer has a thickness of 0.1 to 12.0 μm.

5. 3. The filter material according to claim 1, wherein the first nonwoven fabric layer has a basis weight of 1 to 14 g / m 2 That is, the filter material.

6. 3. The filter material according to claim 1 or 2, wherein the first nonwoven layer is 2-15% of the thickness of the laminate.

7. 3. The filter material of claim 1 or 2, wherein the first nonwoven layer is comprised of a meltblown nonwoven.

8. 3. The filter material of claim 1 or 2, wherein the second nonwoven layer is comprised of a spunbond nonwoven.

9. 3. A filter material according to claim 1 or 2, for filtering oil-containing solids.

10. 3. The filter material according to claim 1 or 2, wherein the first nonwoven fabric layer and the second nonwoven fabric layer both comprise biodegradable fibers.

11. 11. The filter material of claim 10, wherein the biodegradable fibers comprise polylactic acid fibers.

12. 3. A filter vessel comprising the filter material according to claim 1 or 2, the first nonwoven fabric layer being disposed on the inside of the filter vessel.

13. 3. An encapsulation body comprising the filter material of claim 1 or 2 and a substance to be encapsulated, the substance being in contact with a first nonwoven fabric layer.

14. A method for producing a filter material including a laminate composed of a first nonwoven fabric layer and a second nonwoven fabric layer, comprising: Providing a first nonwoven fabric sheet and a second nonwoven fabric sheet; and a step of integrating the first nonwoven fabric sheet and the second nonwoven fabric sheet to obtain a laminate composed of a first nonwoven fabric layer and a second nonwoven fabric layer. the fibers constituting the first nonwoven fabric sheet have an average fiber diameter smaller than that of the fibers constituting the second nonwoven fabric sheet; At least one of the first nonwoven fabric sheet and the second nonwoven fabric sheet is made of biodegradable fibers, The method for producing a filter material, wherein the first nonwoven fabric sheet is in a pressed state.

15. 15. The method for producing a filter material according to claim 14, wherein the step of preparing the first nonwoven fabric sheet comprises the step of obtaining the first nonwoven fabric sheet by pressing.

16. 16. A method for producing a filter material according to claim 14 or 15, wherein the first nonwoven sheet is a pressed meltblown nonwoven.

Citation Information

Patent Citations

  • Biodegradable sheet material for coffee extraction

    JP2000336570A

  • Filter for food made of biodegradable laminate nonwoven fabric

    JP2011157118A

  • Sheet for extraction, filter for extraction, and bag for extraction

    JP2016168569A